Overdose response centering inequity and diversity study: a protocol for assessing the population-level and equity impact of the emergency medical services system changes using critical race theory - Gatanaga, Ohshue S.; Cotta, Nicholas; Waters, Kimiam; Gu, Alden; Heidari, Omeid; Frohe, Tessa; Wettemann, Courteney; Morris, Andre; Rourke, Esther; Ornelas, India; Lamont, Malika; Damper, Deaunte; et al. (Frontiers in Public Health, 2025)
BackgroundStructural racism continues to drive racial disparities in opioid-related deaths by creating inequitable access to healthcare, shaping prescription practices, limiting availability of culturally responsive care, and concentrating socioeconomic disadvantage in racial/ethnic minority communities. Emergency Medical Services (EMS) based interventions provide a critical opportunity to address these disparities at the frontlines of care, as minoritized communities often utilize EMS as their usual source of care. In King County, Washington, EMS has begun implementing several system changes aimed at reducing opioid overdose deaths, promoting harm reduction strategies, increasing access to overdose prevention resources, and improving outcomes for individuals who survive overdoses. The Overdose Response Centering Inequity and Diversity (ORCID) study will evaluate these EMS system changes to understand their impact on opioid-related outcomes differentially by race and ethnicity.MethodsThis study employs a mixed-methods, hybrid effectiveness-implementation design with three aims: (1) to understand experiences and outcomes for minoritized racial groups at the patient level using a prospective cohort study (n = 500) of non-fatal overdose survivors; (2) to evaluate EMS system changes’ implementation processes from the perspectives of Black, Hispanic/Latinx, and American Indian/Alaska Native non-fatal overdose survivors using in-depth interviews (n = 60); and (3) to examine population-level impacts of EMS system changes on racial disparities using secondary data from King County EMS. Utilizing an innovative community-based participatory approach, this study centers and incorporates individuals with lived and living experience of drug use as equal partners throughout the research process.DiscussionThrough a rigorous evaluation of EMS system changes in King County, this study will generate actionable insights for improving EMS responses to the opioid epidemic and addressing racial disparities both locally and nationally. As one of the first studies to track a longitudinal cohort of non-fatal overdose survivors, ORCID will provide critical data on both short- and long-term outcomes, informing future interventions focused on improving continuum of care for overdose survivors. By employing a community-engaged approach, the study centers the lived experiences of those most affected and enhances the relevance of the study findings. Potential limitations include the rapidly evolving landscape of EMS interventions and biases associated with non-random sampling.